Digital Transformation and the Fight against Corruption in Nigeria’s Public Sector - Agaptus Nwozor; Modupe Ake; Oladapo Joy Oluwakemi; Ayanrinde Racheal Tijesunimi (Universitas Medan Area, 2022)
Digital transformation is an increasingly strategic theme in public sector governance throughout the world. The advancement in information communication and technology (ICT), especially its expansion to every area of life, has elicited great interests due to its capacity to contribute to efficient service delivery generally. Across the world governments have embraced the digitalization of their operations, and have therefore achieved greater efficiency in government business. In this paper content, digital transformation of the public sector of Nigeria entails the application of modern information technology to its operational processes with a view to enhancing its capacity for efficiency, and thus deal with leakages that conduce to corrupt practices. Digital transformation offers the opportunity for an intelligent use of the ICT for organizational efficiency. Corruption has remained one of the most complex problems impeding Nigeria’s development. The overarching objective of this paper is to assess the nature of digital transformation in the Nigerian public sector, mechanisms and challenges of fighting corruption. Using primary data generated through key informant interviews and complemented with secondary data, this paper specifically interrogates the factors that conduce to, or inhibit the digitalization of Nigeria’s public sector as well its overall implication in the fight against corruption. This paper finds that the digitalization of public sector will likely improve transparency in the operating activities of the public sector and thus lead to the elimination of corruption. This paper recommends, among others, the digitalization of public sector operations and the strengthening of institutions having direct and indirect mandate to fight corruption.